Study on the Damage Behavior of Engineered Cementitious Composites: Experiment, Theory, and Numerical Implementation - Tingting Ding; Zhuo Wang; Yang Liu; Xinlong Wang; Tingxin Sun; Shengyou Yang (CivilEng)
The ever-increasing material performance requirements in modern engineering structures have thrust engineered cementitious composites (ECCs) into the limelight of civil engineering research. The exceptional tensile, bending, and crack-control abilities of ECCs have sparked significant interest. However, the current research on the mechanical behavior of ECCs primarily focuses on uniaxial tensile and compressive constitutive relationships, leaving a gap in the form of a comprehensive multidimensional constitutive model that can fully describe its complex behavior at large strains. This study rigorously addresses this gap by initially investigating the uniaxial tensile and compressive behavior of ECCs through experiments and establishing a one-dimensional constitutive relationship of ECCs. It then introduces the concepts of damage energy release rate and energy equivalent strain, and constructs a three-dimensional constitutive model of ECCs by introducing the damage variable function. We write the numerical algorithm of our theoretical model in terms of the VUMAT subroutine and implement it into ABAQUS 2019 finite element software. We validate the accuracy and practicality of the multidimensional constitutive model by comparing the experimental data of uniaxial tension/compression and four-point bending. This paper enriches the theoretical system of ECCs and provides rigorous guidance for the performance optimization and practical application of such advanced engineering materials.